2020
DOI: 10.3390/ijerph17196980
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Universal Screening for Postnatal Depression in South Africa: Confirmation from a Sub-District in Pretoria, South Africa

Abstract: Although postnatal depression (PND) is a worldwide public health problem, it is relatively higher in developing countries, including countries in Sub-Saharan Africa. Postnatal depression is not routinely screened for in primary healthcare facilities in South Africa, despite its reported compromise on mother and child health. The purpose of this study was to determine the prevalence of, as well as factors associated with, postnatal depression in a sample of clinic attendees in a sub district in Tshwane, South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…As PDE may have potentially long-term impact, it is important that maternal depression be identified and addressed early. This is especially pressing in LMIC settings such as our study setting, where rates of depression are much higher than in the general population (Mokwena & Masike, 2020 ), and where psychological interventions may be useful (Gajaria & Ravindran, 2018 ). The rate of depression in our larger DCHS cohort of 28% coincide with the higher rates in LMIC.…”
Section: Discussionmentioning
confidence: 99%
“…As PDE may have potentially long-term impact, it is important that maternal depression be identified and addressed early. This is especially pressing in LMIC settings such as our study setting, where rates of depression are much higher than in the general population (Mokwena & Masike, 2020 ), and where psychological interventions may be useful (Gajaria & Ravindran, 2018 ). The rate of depression in our larger DCHS cohort of 28% coincide with the higher rates in LMIC.…”
Section: Discussionmentioning
confidence: 99%
“…This indicate that the PND prevalence rate in this study is comparable but slightly higher than that of women attending the public hospitals which is expected since the mothers in this sample were exclusively from the slum settings and therefore extreme poverty. Recent research findings from other African countries show a high PND prevalence rates: Rwanda 63.6%, South Africa (57.14%) [ 35 ] and (38.8%) [ 36 ], Nigeria 35.6% [ 37 ]. Comparable to our finding, a systematic review and meta-analysis revealed a prevalence rate of 26% in Middle-East countries, while European countries had lower rates (8%) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The validity in the study was enhanced by the use of the EPDS, which is an already valid, reliable, and standardised tool for screening of PND. 22 The EPDS tool has been used in previous South African studies. 13,30,49 Nonetheless, the tool was validated through content and face validity and a pilot study.…”
Section: Data Collection Tool and Recruitmentmentioning
confidence: 99%
“…20 Although the negative impact of PND on both mother and child is well documented, 21 this area of maternal mental health has not enjoyed adequate attention in many countries, including South Africa. 22 The symptoms of PND can be easily identified by the use of the EPDS, a well-validated screening tool that is used in many countries. 23 Although this tool is economical and easy to use, PND is not routinely screened for in primary healthcare settings in South Africa.…”
Section: Introductionmentioning
confidence: 99%